Inclusão de deficientes visuais no ensino de geometria plana - Oliveira, Larissa Katharine de [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
O intuito deste trabalho é a inclusão de alunos com deficiência visual no aprendizado de Matemática. Assim, buscamos elaborar um material com os conceitos referentes ao ensino de Geometria Plana para o 8º ano do Ensino Fundamental, segundo os materiais do FTD Sistema de Ensino, voltados a alunos com este tipo de deficiência. Entretanto, o trabalho também aborda, de maneira concisa, conceitos aprendidos em anos escolares anteriores essenciais para o aprendizado dos conteúdos propostos, concomitantemente com os embasamentos matemáticos fundamentais para o desenvolvimento do professor. Através de atividades e algumas demonstrações práticas com material concreto, mostra-se possível o ensino de Geometria Plana a um aluno com deficiência visual de modo prazeroso e eficaz.

The purpose of this study is the inclusion of students with visual impairment in learning of Mathematics. Thus, we seek to elaborate a material with the concepts related to the teaching of Plane Geometry for the 8th grade of Elementary School, according to the materials of the FTD Teaching System, aimed at students with this type of disability. However, the work also concisely addresses concepts learned in previous school years essential for the learning of the proposed contents, simultaneously with the fundamental mathematical foundations for teacher’s development. Through activities and some practical demonstrations with concrete material, it is shown to be possible to teach Plane Geometry to a student with visual impairment in a pleasant and effective way.
Inclusion of the visually impaired in the teaching of plane geometry
Keywords: Geometria plana; Deficiência visual; Material concreto; Plane geometry; Visual impairment; Concrete material